2019
DOI: 10.4236/ajor.2019.94010
|View full text |Cite
|
Sign up to set email alerts
|

A Min-Max Strategy to Aid Decision Making in a Bi-Objective Discrete Optimization Problem Using an Improved Ant Colony Algorithm

Abstract: A multi-objective optimization problem has two or more objectives to be minimized or maximized simultaneously. It is usually difficult to arrive at a solution that optimizes every objective. Therefore, the best way of dealing with the problem is to obtain a set of good solutions for the decision maker to select the one that best serves his/her interest. In this paper, a ratio min-max strategy is incorporated (after Pareto optimal solutions are obtained) under a weighted sum scalarization of the objectives to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…where P busy j and P idle j represent the power usage of server j under full and no-load conditions, respectively. U cpu j represents the CPU utilization on physical node j [22]. Next, this paper analyzes the optimization problem of virtual machine initialization deployment.…”
Section: Virtual Machine Of the Multiobjective Ant Colony Improved Al...mentioning
confidence: 99%
“…where P busy j and P idle j represent the power usage of server j under full and no-load conditions, respectively. U cpu j represents the CPU utilization on physical node j [22]. Next, this paper analyzes the optimization problem of virtual machine initialization deployment.…”
Section: Virtual Machine Of the Multiobjective Ant Colony Improved Al...mentioning
confidence: 99%
“…Studies in bi-objective optimization constitute a non-trivial part in multi-objective analyses. For instance, Zhou et al [1], Kukkonen and Deb [2], Pinto-Varela et al [3], Lath et al [4], Pereyra et al [5], Garg [6], Futrell et al [7], Hirpa et al [8], Liu et al [9], Wang et al [10], Cheraghalipour et al [11], Ho-Huu et al [12], Yeh [13], Liu et al [14], Nagamanjula and Pethalakshmi [15], Xu et al [16], Diao et al [17], Mohammadi et al [18], Kparib et al [19], Kparib et al [20], Gulben and Orhan [21], Zaninudin and Paputungan [22], and Stutzle and Hoos [23]. Studies proposing multi-objective optimization techniques and solution can be found in Messac [24], Das and Dennis [25], Deb [26], Messac et al [27], Messac and Mattson [28], Kim and Weck [29], Zhang and Li [30], Chinchuluun and Pardalos [31], Mueller-Gritschneder et al [32], Pereyra et al [5], Pérez-Fernández et al [33], Marler and Arora [34], Gunantara [35], Orths et al [36], Collette and Siarry [37], Ehrgott [38], Eskelinen et al [39], Fonseca and Fleming [40], Alaa et al…”
Section: Introductionmentioning
confidence: 99%